How do Chinese tourists perceive tranquillity during the tour?. (April 2020) - Hu, Meng; Zhang, Yingying; Zhang, Hui; Lu, Youhai; Zuo, Lin; Zhuang, Min; Liu, Wei; Zhang, Jie; Zhang, Honglei
Abstract: Tranquillity is considered a preferred travel experience for people. Despite there are many researches on the measurement and evaluation of tranquillity, little has explored the perception of tranquillity during the tour. Through the study of Chinese tourists, we try to cover the gap by exploring how tourists perceive tranquillity in different tranquil areas. This study expounds the Chinese understanding of tranquillity and adopts the grounded theory to systematically analyse the real experience of tourists. The study summarizes 3 major categories and 20 types of tranquil areas. The environmental characteristics of tranquil areas are classified into 4 dimensions: quietness, stable society, natural scenery and local culture. We propose a geographical process of perceiving tranquillity in tourist destinations, which includes the relationship between tourists and motivation, environment (landscape and soundscape), behaviour, emotion and psychological activities. These relations are helpful to provide a new perspective on tranquillity outside the post-positivist research paradigm. Highlights: The geographical process of tourists' perception of tranquillity is clarified. The article makes a comparison between Chinese and western understanding of tranquillity. Landscape and soundscape spectrums covering 20 types of tranquil areas are collected. The relationship between tranquillity and tourists' behavior and emotion are proposed.